2018
DOI: 10.5740/jaoacint.17-0445
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Escherichia coli from Farm Livestock and Related Analytical Methods: A Review

Abstract: The indiscriminate use of antibiotics for the treatment of human and animal infections has led to the rise of resistance in pathogens and in commensal bacteria. In particular, farm animals may act as vectors for the dissemination of drug-resistant genes because of the intensive use of antibiotics in animal production, enabling resistance to a wide range of antimicrobial agents, including those normally used in human medicine. Escherichia coli, being a widespread commensal, is considered a good indicator of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…In fact, E. coli is one of the most significant global concerns in human and animal health sectors, the food industry and in the environment (Paitan, 2018). AMR surveillance programs have indicated that resistance to all the major classes of antibiotics now circulate among E. coli strains (Pitout, 2012), including extended-spectrum β-lactams (ESBL), carbapenems, and more recently, plasmid-mediated colistin resistance (mcr-1), particularly in food animals from China and Vietnam (Liu et al, 2016;Huang et al, 2017;Caruso, 2018). The ubiquitous nature of E. coli means it constitutes a shared reservoir for AMR across a One Health framework, and concerns have been raised about the possible transmission of AMR E. coli between animals and humans through direct contact or via the food chain (Poirel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, E. coli is one of the most significant global concerns in human and animal health sectors, the food industry and in the environment (Paitan, 2018). AMR surveillance programs have indicated that resistance to all the major classes of antibiotics now circulate among E. coli strains (Pitout, 2012), including extended-spectrum β-lactams (ESBL), carbapenems, and more recently, plasmid-mediated colistin resistance (mcr-1), particularly in food animals from China and Vietnam (Liu et al, 2016;Huang et al, 2017;Caruso, 2018). The ubiquitous nature of E. coli means it constitutes a shared reservoir for AMR across a One Health framework, and concerns have been raised about the possible transmission of AMR E. coli between animals and humans through direct contact or via the food chain (Poirel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of antibiotics into the medical practice field was one of the major achievements contributing to the significant reduction of morbidity and mortality due to communicable diseases (Caruso, 2018). Antimicrobial agents include a wide variety of pharmaceutical and natural substances that exhibit antimicrobial activity against bacteria, protozoa, viruses, and fungi (Leekha, Terrell, & Edson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are accumulating reports from different regions around the globe about the emergence of multidrug-resistant bacteria in different livestock species. Subsequently, food animals are also shown to be responsible for accelerating the spread of AMR bacteria to humans and environment (Caruso, 2018); (Threlfall, Ward, Frost, & Willshaw, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli present in humans and animals' gut is considered an indicator, which provides hints on the emergence and dissemination of drug resistance. The frequency of resistance in commensal E. coli is considered a useful marker for the selective pressure applied by antibiotic use and the future resistance predicted in pathogens 11 . LMICs have a high AMR burden, and optimal interventions are hampered by a lack of surveillance 12 .…”
mentioning
confidence: 99%